Amalan Pengurusan Perniagaan Usahawan Tani IKS Bumiputera: Satu Kajian Kes di Negeri Terengganu. (Sains Humanika, 2011)
Agriculture in this country is experiencing significant transformation towards a more dynamic and competitive sector. This sector is critical in the sense that it is not only contributingto economic growth but also to creating job opportunities. The development of agro-based small and medium industries (SMI) is emphasised the nation's Agriculture Policy because it is expected to value add the agro-products. Even tough the move by the government to make Malaysia a global hub for food production and chain by 2010, the achievement of SMI Bumiputera agropreneurs is still at low level. This case study utilised quantitative and qualitative approaches. Based on the research objectives and literature review, a set ofÂ  questionnaires, interview protocol and site visit checklist was developed in order to collect pertinent data for this study. A sample of 10 agropreneurs (5 males and 5 females) in the state of Terengganu was selected based on their success profile in the business. The study found that the respondents strongly agreed (m=4.43, sd=0.55) that their business practices were in order. However, the result of the interview reveals that the participants acknowledged that their marketing strategies were weak. Further, the results of the site visit and document analysis show that, in general, the participants' management offinances and account were poor.
Keywords: Agriculture; small and medium industries (SMI); agropreneurs; Bumiputera; Malaysia